Sufficient conditions for the blowup of a solution to the Boussinesq equation subject to a nonlinear Neumann boundary condition - Korpusov, M. O.; Sveshnikov, A. G. (Computational mathematics and mathematical physics, 2008)
Sufficient blowup conditions are obtained for a solution to the generalized Boussinesq equation subject to a nonlinear Neumann boundary condition.